EFFECT OF INCREASING USE THE CARD PAYMENT EQUIPMENT ON THE INDONESIAN ECONOMY - Tiara Nirmala; Tri Widodo (Jurnal Bisnis dan Ekonomi, 2011)
Non-cash payments have been increasing significantly, followed by its substitution andefficiency effects. Cash payment is substituted, inducing a decrease of cash holding by economicagents, while on the other hand more money enters the banking system. The increase of non-cashpayments also cuts transaction costs, and the economy runs more efficiently. Using Vector ErrorCorrection Model (VECM), its impacts on the economy are investigated. The result shows thatcash holdings decrease, while money stock M1 and M2 increase. The increase of non-cashpayments also induces GDP growth and slight price decrease.Keywords: non-cash, payment system, money demand, JEL: E42, E52